Research on longitudinal resolution of loop source transient electromagnetic method - Tao XING; Zhihai JIANG; Lele MENG; Peiyu LI (Meikuang Anquan)
The loop source transient electromagnetic method has been widely applied in the hydrogeological exploration of coal mines, such as demarcating impermeable layers, detecting waterlogged goaf areas, and evaluating hydro-geological parameters. In recent years, both the theory and technology of transient electromagnetic method have made considerable progress. However, the exact detection and resolution capabilities remain unclear, which has affected the design of transient electromagnetic method schemes and the interpretation of data. In response to this, H and K-type geoelectric models were established. Through numerical calculations, quantitative analysis of the longitudinal resolution ability of the transient electromagnetic method by electrical differences, burial depth, and loop side length were carried out. Regression analysis was introduced to establish an evaluation model for the thin-layer detection ability of transient electromagnetic in loop sources, achieving quantitative prediction of resolution. The research results show that the electrical property difference is a key factor affecting the detection depth and resolution. As the electrical property difference increases, the sensitivity value increases, and the resolution of the loop source transient electromagnetic method improves. For the transmission loop with a side length of 100 meters, when the burial depth is 100 meters and the electrical property ratio to the surrounding rock is 1∶2, a low-resistance layer of 6.44 meters can be identified. When the electrical property ratio to the surrounding rock is 1∶4, a low-resistance layer of 2.1 meters can be distinguished.